Age effects on preattentive and early attentive auditory processing of redundant stimuli: is sensory gating affected by physiological aging? - Gmehlin, Dennis; Kreisel, Stefan H.; Bachmann, Silke; Weisbrod, Matthias; Thomas, Christine (The journals of gerontology. Series A, Biological sciences, medical sciences, 2011)
The frontal hypothesis of aging predicts an age-related decline in cognitive functions requiring inhibitory or attentional regulation. In Alzheimer’s disease, preattentive gating out of redundant information is impaired. Our study aimed to examine changes associated with physiological aging in both pre- and early attentive inhibition of recurrent acoustic information. Using a passive double-click paradigm, we recorded mid-latency (P30-P50) and late-latency (N100 and P200) evoked potentials in healthy young (26 ± 5 years) and healthy elderly subjects (72 ± 5 years). Physiological aging did not affect auditory gating in amplitude measures. Both age groups exhibited clear inhibition in preattentive P50 and attention-modulated (N100) components, whereas P30 was not attenuated. Irrespective of age, the magnitude of inhibition differed significantly, being most pronounced for N100 gating. Inhibition of redundant information seems to be preserved with physiological aging. Early attentive N100 gating showed the maximum effect. Further studies are warranted to evaluate sensory gating as a suitable biomarker of underlying neurodegenerative disease.
Advance access published on July 25, 2011
Gesehen am 27.06.2022